1983
DOI: 10.1128/aem.45.6.1790-1794.1983
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Carrier and Temperature on Survival of Rhizobium spp. in Legume Inocula: Development of an Improved Type of Inoculant

Abstract: The effects of inoculant carrier, temperature, and storage period on the survival of Rhizobium strains were determined by plate count and most-probable-number analyses. Preliminary experiments showed that survival of rhizobia was affected by each of these factors and their interactions. Results offurther studies indicated that six strains of rhizobia survived better at high temperatures when lyophilized and suspended in an oil carrier as compared to finely ground peat. The oil base

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0
2

Year Published

1985
1985
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(15 citation statements)
references
References 11 publications
2
9
0
2
Order By: Relevance
“…These results confirm previous works (Mary et al 1985;Mugnier and Jung 1985;Mary et al 1986). The harmful effects of temperature on survival of Rhizobiaceae in the dried state currently described in the literature (Kremer and Peterson 1983;Juwarkar and Rewari 1988;Pesenti-Barili et al 1991) were also observed in this study although satisfactory survival rates were obtained during storage at 3% RH. The conjunction of high RHs ( > 44%) and relatively high temperature resulted in linear decreases in survival rates as previously described (Mary et al 1985;Juwarkar and Rewari 1988).…”
Section: Nodulation and Nitrogen Fixation By Spray-dried Bradyrhizobisupporting
confidence: 75%
See 1 more Smart Citation
“…These results confirm previous works (Mary et al 1985;Mugnier and Jung 1985;Mary et al 1986). The harmful effects of temperature on survival of Rhizobiaceae in the dried state currently described in the literature (Kremer and Peterson 1983;Juwarkar and Rewari 1988;Pesenti-Barili et al 1991) were also observed in this study although satisfactory survival rates were obtained during storage at 3% RH. The conjunction of high RHs ( > 44%) and relatively high temperature resulted in linear decreases in survival rates as previously described (Mary et al 1985;Juwarkar and Rewari 1988).…”
Section: Nodulation and Nitrogen Fixation By Spray-dried Bradyrhizobisupporting
confidence: 75%
“…Drying and protracted storage did not affect the symbiotic properties of B. japonicum. Dye (1982) and Kremer and Peterson (1983) came to similar conclusions although in the report of Dommergues et al (1979) loss of infectiveness has been observed.…”
Section: Nodulation and Nitrogen Fixation By Spray-dried Bradyrhizobisupporting
confidence: 60%
“…In some reports, the rhizobium population fell markedly as most of the water was lost. This rapid decline in survival was followed by a period with a slower death rate (11,17,20,24).…”
Section: Discussionmentioning
confidence: 99%
“…This probably accounts for the failure to recover cells grown on MSY, which supported polysaccharide production, and for the considerable improvement in recovery yields when yeast extract alone was the growth medium. Freeze-drying has been used successfully in the long term storage of stock cultures (Dye 1982) and in the production of inoculants (McLeod & Roughley 1961;Kremer & Peterson 1983). It is not widely used for this purpose, however, although it has the advantage of producing a concentrated inocu-lant with a long shelf-life particularly at higher temperatures.…”
Section: Discussionmentioning
confidence: 99%